Gender dimensions of solid and liquid waste management for reuse in agriculture in Asia and Africa - Taron, Avinandan; Drechsel, Pay; Gebrezgabher, Solomie A. (International Water Management Institute, 2021)
This report examines social equality aspects related to resource recovery through solid waste composting and wastewater irrigation. The report shows that women are represented in greatest numbers at the base of the recycling chain, most often as informal waste pickers and as sorters of recyclables with limited access to resources and upward mobility. Despite a wide gender gap in the solid waste and sanitation sectors, women play a key role in both municipal waste reduction and food safety where irrigation water is unsafe. Analyzing the gender dimension is important for understanding household responses to recycling programs, differences between the formal and informal sectors as well as along the waste-to-resource value chain from collection to treatment and reuse. The report stresses the important role of women in household waste management, including waste segregation, and the power of women-dominated waste picker associations, where the informal sector plays an essential role alongside the formal sector.